Seasonal changes in stress biomarkers of an exotic coastal species – Chaetopleura angulata (Polyplacophora) – Implications for biomonitoring. Issue 1 (15th July 2017) - Madeira, Diana; Vinagre, Catarina; Mendonça, Vanessa; Diniz, Mário Sousa
Abstract: Knowledge on baseline values of stress biomarkers in natural conditions is urgent due to the need of reference values for monitoring purposes. Here we assessed the cellular stress response of the chiton Chaetopleura angulata in situ . Biomarkers commonly used in environmental monitoring (heat shock protein 70 kDa, total ubiquitin, catalase, glutathione-S-transferase, superoxide-dismutase, lipid peroxidation) were analyzed in the digestive system, gills and muscle of C. angulata, under spring and summer conditions in order to assess seasonal tissue-specific responses. Season had an effect on all targeted organs, especially affecting the digestive system which displayed clear seasonal clusters. The respective Integrated Biomarker Response (IBR) showed a 7.2-fold seasonal difference. Muscle and gills showed similar IBRs between seasons making them appropriate organs to monitor chemical pollution as they were less responsive to seasonal variation. The most stable biomarkers in these organs were ubiquitin and superoxide-dismutase thus being reliable for monitoring purposes. Graphical abstract: Highlights: Stress biomarkers were assessed in a bioindicator chiton for monitoring purposes . The digestive system, gills and muscle of chitons were sampled in spring and summer. Season had an effect on all targeted organs. Muscle and gill can be used to monitor chemical pollution. Tub and SOD are the most reliable biomarkers to monitor chemical pollution.